Characterization of Escherichia coli Cefotaxime-Resistance in Al-Ahsa, KSA: Predominance of CTX-15 and First Report of blaCMY-42 Gene - Melek Ben Aissa; Sana Ferjani; Mohamed Salah Abassi; Nada Al-Suwailem; Ilhem Boutiba (Applied Sciences, 2022)
We determined an antibiotic resistance mechanism in the eastern region, KSA, and the genetic factor clonal relatedness within Gram-negative bacteria. During our retrospective study, a total number of 29 E. coli ESBL producer strains were isolated for patients visiting King Fahad Hospital, Al-Ahsa, KSA. The bla genes were detected via PCR and identified via sequencing. Associated plasmid-mediated quinolone resistance genes, as well as int1 and int2 genes, were also studied. Phylogenetic groups, the ST131 clone, virulence factors, and PFGE were also checked. The blaCTX-M-9 (3.7%), blaCTX-M-27 (22.2%), and blaCTX-M-15 (77.8%) genes were identified; however, the blaCMY-42 (7.4%) gene was recorded for the first time in KSA. The qnrS1 gene was found in 44.4% of strains, and among them, 50% concomitantly harbored the aac(6′)Ib-cr. The int1 gene was detected in 25.9% strains; nonetheless, the int2 gene was found in 7.4% of isolates. The strains belonged mainly to the B2 and D phylogroups. PFGE showed unrelated patterns. Some isolates belonged to the pandemic clone ST131. We describe a large dissemination of antibiotic resistance to third-generation cephalosporins in the eastern region, KSA, with the occurrence of the blaCMY-42 gene. The clone ST131 seems to be the principal contributor for blaCTX-M-15 gene spread.